c.1 - "Koestlert, Arthur" (London, 1984)
The manuscript of Stranger on the Square was found among Arthur Koestler's papers after their deaths. It was not then in publishable form and some of the material has subsequently been re-arranged and edited. However, nothing essential has been eliminated and Cynthis Koestler's sections of the book are frank about her life with Arthur, his love affairs, his demanding nature, his temper, his depressive moods and his manic activity from time to time.
Keywords: "Koester, Arthur, 1905-Biography"